The Effect of Digital Marketing-Based Entrepreneurship Instructional Videos on the Sales Intent for Fashion Products Using an Affiliate Program - Apriliyanawati, Adilla; Irianti, Agus Hery Supadmi; Sulistyaningwati, Bhindri; Alimah, Alimah (Education and Development Research, 2026)
This study aims to examine the effectiveness of digital marketing-based entrepreneurship instructional videos integrated with an affiliate program on the sales intent for fashion products among students one of the state vocational high schools in East Java, Indonesia. The research employed a development method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through pre-test and post-test instruments to measure changes in student entrepreneurial interest, alongside expert validation questionnaires to assess the media's feasibility. The expert validation results indicated that the instructional videos are highly feasible, with an average score of 97%. The pre-test results showed that students' entrepreneurial interest was in the very low category (53.2%); however, it increased to the moderately high category (84%) following the implementation of the instructional videos. It is concluded that this instructional video media is highly practical and effective in increasing students' entrepreneurial interest.